2018
DOI: 10.1186/s40413-018-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Confounders of severe asthma: diagnoses to consider when asthma symptoms persist despite optimal therapy

Abstract: Asthma can often be challenging to diagnose especially when patients present with atypical symptoms. Therefore, it is important to have a broad differential diagnosis for asthma to ensure that other conditions are not missed. Clinicians must maintain a high index of suspicion for asthma mimickers, especially when patients fail to respond to conventional therapy. The purpose of this review is to briefly review some of the more common causes of asthma mimickers that clinicians should consider when the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 93 publications
1
17
0
2
Order By: Relevance
“…The difficulty can start with the first step, which is proper confirmation of asthma diagnosis. Additionally, in many patients with difficult-to-control asthma, other factors may contribute to poor control, including GERD, vocal cord dysfunction, the use of beta-blockers or ACE-Is, anxiety, depression, obesity, or proper inhaler technique [ 3 , 31 , 32 ]. Before escalating therapy with the addition of biologics in patients whose disease is uncontrolled, current GINA 2020 guidelines recommend proper asthma diagnosis and thorough evaluation to exclude masquerading diseases and contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty can start with the first step, which is proper confirmation of asthma diagnosis. Additionally, in many patients with difficult-to-control asthma, other factors may contribute to poor control, including GERD, vocal cord dysfunction, the use of beta-blockers or ACE-Is, anxiety, depression, obesity, or proper inhaler technique [ 3 , 31 , 32 ]. Before escalating therapy with the addition of biologics in patients whose disease is uncontrolled, current GINA 2020 guidelines recommend proper asthma diagnosis and thorough evaluation to exclude masquerading diseases and contributory factors.…”
Section: Discussionmentioning
confidence: 99%
“…According to pulmonologists' experiences, our results indicated that Croatian GPs rarely undertake diagnostic procedures to verify asthma quantitatively. In patients with SA, in addition to non-recognition of asthma mimickers, the main barrier to correct diagnosis is poor recognition and comprehension of the severity of the disorder [21,22]. This lack of appropriate testing and lack of recognition often result in delayed [21,23].…”
Section: Plos Onementioning
confidence: 99%
“…Treatable traits focusing on extrapulmonary and psychosocial aspects have to be checked and addressed at that stage (primary care). If asthma remains poorly controlled (difficult-to-treat asthma), asthma specialists will be involved to optimize inhaled treatment, reassess differential diagnosis and check and address more treatable traits, especially pulmonary traits (secondary care) (7). When these steps are achieved, if asthma is still uncontrolled, a biologic can be considered as an alternative or add on to a low dose of daily steroids.…”
Section: From Phenotypes To Targeted Therapies: Toward Deciphering Mumentioning
confidence: 99%
“…(iii) Do any asthma comorbidities remain uncontrolled? (7). Should a pharmacological treatment step-up strategy or a nonpharmacological approach (allergen or occupational avoidance, smoking cessation, anxiety-controlling strategies, respiratory rehabilitation) be considered?…”
Section: Introductionmentioning
confidence: 99%